Psychological effects of social media on Muslim youths in northern Nigeria - Adamu Abubakar Muhammad; Ikilima Abubakar Shariff; Yakubu Zulaihat Muhammed; Muhamad Subhi Apriantoro (Ethica: International Journal of Humanities and Social Science Studies, 2024)
This study examines the psychological effects of social media on Muslim youths in Northern Nigeria. By taking an in-depth look at the growth of social media in the region, its use by Muslim youths, and its effects on their psychological well-being, this study seeks to contribute to the body of knowledge regarding the psychological impact of social media use. In order to understand this phenomenon, we conducted qualitative interviews with 22 Muslim youths in northern Nigeria. Results indicate that the majority of participants believe that social media use has a negative effect on their psychological well-being, with many citing feelings of anxiety, depression, and insecurity when using social media frequently. Further, results showed that many participants reported feelings of alienation from the local communities, since they often felt that they were judged for their online behavior due to the false impressions created by social media. Overall, this study demonstrates the degree to which social media has infiltrated the lives of many Muslim youths in Northern Nigeria and how its effects may be both positive and negative. It is important to recognize the potential psychological effects of social media use in this population and to equip Muslim youths with the necessary resources to navigate its use in a healthy way.